The Influence of Product Quality, Brand Image and E-Wom on Makeup Product Purchase Decisions By Lizzie Parra (BLP) - Fadilah, Nayla Nur; Wijayaningsih, Rini; Handayani, Milda (PT.KARYA GEMAH RIPAH, 2025)
This study aims to determine the influence of product quality, brand image, and e-WOM on purchase decisions of makeup By Lizzie Parra (BLP) products (case study of BLP customers at Summarecon Mall Bekasi). This research is a quantitative study using primary data collected through questionnaires distributed directly to customers who have purchased and experienced BLP products at Summarecon Mall Bekasi. A total of 100 questionnaires were distributed. Based on statistical tests, the results show that Product Quality has a significant value (sig.) of 0.000, which is less than 0.05, and a t-count value of 4.231, which is greater than the t-table value of 1.98498, with a positive sign. Thus, hypothesis H1 is accepted, indicating that Product Quality has a positive influence on Purchase Decisions. Brand image has a significance value (sig.) of 0.010, which is less than 0.05, and a t-count value of 2.615, which is greater than the t-table value of 1.98498, with a positive sign. Thus, hypothesis H2 is accepted, indicating that Brand image has a positive influence on Purchase Decisions. e-WOM has a significant value (sig.) of 0.039, which is less than 0.05, and a t-count value of 2.097, which is greater than the t-table value of 1.98498, with a positive sign. Thus, hypothesis H3 is accepted, indicating that e-WOM has a positive influence on Purchase Decisions. For the simultaneous test, Product Quality, Brand image, and e-WOM have a significant value (sig.) of 0.000, which is less than 0.05. Therefore, hypothesis H4 is accepted, indicating that these three variables simultaneously have a significant influence on Purchase Decisions.